Pengaruh Teman Sebaya dan Keterampilan Mengajar Dosen Terhadap Motivasi Belajar Mahasiswa Pendidikan Ekonomi Angkatan 2021-2022 Universitas PGRI Wiranegara - Andjani Sulistyaningrum Kinasih; Sugeng Pradikto (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Motivation is very important for improving learning. Achieving learning goals requires motivation. Motivated students will definitely improve the quality of their learning and achieve better. In the learning process, of course, there are peers and lecturers as educators. This research examines how peers and lecturers' teaching skills influence the learning motivation of Economics Education students at PGRI Wiranegara University, especially for the Class of 2021–2022. This research uses quantitative research methods. The data collection technique uses a questionnaire with a Likert scale. There were 20 students as respondents for this research. Data were analyzed using multiple linear regression techniques. The results of the research show that the simultaneous influence of peers and lecturers' teaching skills on learning motivation is 43.8%. Partially, the peer variable (X1) does not influence learning motivation because the significance value is 0.400 which is greater than 0.05. Meanwhile, the lecturer's teaching skills variable (X2) significantly influences learning motivation because its value is 0.001 which is smaller than 0.05.